PENGARUH IKLAN DIGITAL DAN KUALITAS PRODUK TERHADAP KEPUTUSAN UMKM UNTUK MEMBELI KEBAYA - Gea, Tolona; Hulu, Noritarni; Ginting, Maretta (UNIVERSITAS SARI MUTIARA INDONESIA, 2024)
This. Study. Aims. to determine how consumers' decisions to purchase Agape Tailor UMKM kebaya goods at Medan's Petisah Market are influenced by digital marketing and product quality. The sample and research consisted of 95 people, including clients and staff of the Agape tailors at the Petisah Medan market. Non-probability sampling is the sampling strategy used, and multiple linear regression analysis is the data processing method used. The results of the study indicate that the variables of digital marketing (X1) and product quality (X2) have a significant and positive impact on the variables of purchasing decision (Y) and digital marketing, respectively. (Y), whereas the purchasing decision variable is positively and significantly impacted by the product quality variable (X2). The value of Fcount (14.242)> Ftable (3.09), or sig. equal to 0.000 < 0.05, indicates that each variable has an impact at the same time. The variables of Product Quality and Purchasing Decision account for 64.8% of the explanation of digital marketing. SPSS V26 software tools are used to statistically process the data.